2015
DOI: 10.1155/2015/984528
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcome after Treatment for High-Grade Cervical Lesions: A Retrospective Monoinstitutional Cohort Study

Abstract: Background. The aim of this retrospective observational study of women treated for cervical intraepithelial neoplasia grade 2 or worse (CIN2+) was to assess the long-term risk of residual/recurrent high-grade CIN. Materials and Methods. We evaluated 760 women treated by loop electrosurgical excision procedure (684) or conization (76) between 2000 and 2009, and followed up to June 30, 2014 (median follow-up 6.7 years, range 4–14). Visits every 6 months for the first year after treatment and yearly for up to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The most important part of cervical cancer secondary prevention is not just identifying and treating precancer but also allowing for sequential follow-up of women who screen positive and/or treated for precancerous lesions 4. Follow-up entails treatment of the lesions and post-treatment surveillance to monitor lesion recurrence 5. The purpose of this study was to understand the barriers and facilitators to post-cervical cancer screening follow-up among individual patients and groups of nurses who care for them.…”
Section: Introductionmentioning
confidence: 99%
“…The most important part of cervical cancer secondary prevention is not just identifying and treating precancer but also allowing for sequential follow-up of women who screen positive and/or treated for precancerous lesions 4. Follow-up entails treatment of the lesions and post-treatment surveillance to monitor lesion recurrence 5. The purpose of this study was to understand the barriers and facilitators to post-cervical cancer screening follow-up among individual patients and groups of nurses who care for them.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have evaluated clinical and pathological predictors of the persistence of or residual CIN and cervical cancer. 3,[5][6][7][8][9][10][13][14][15][16][17] However, only a few studies have examined whole uterine specimens after hysterectomy 13 and have focused on post-menopausal patients alone. These studies differ from each other methodologically, including the study populations and analysis of variables.…”
Section: Dovepressmentioning
confidence: 99%
“…2 Studies have reported that residual disease or recurrence of CIN 2+ after treatment ranges from 1.1% to 17.7%. [3][4][5][6][7][8][9][10][11] In addition, the risk for cervical cancer in patients treated for CIN 2-3 can be fivefold higher than that in the general population. 12 Therefore, to make more appropriate management decisions in clinical practice, many researchers have investigated risk factors that may predict residual disease after treatment for CIN 2-3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidences of CIN and cervical cancer, therefore, are increasing in those countries, especially among women of reproductive ages, which leaves cervical cancer still among the leading causes of cancer-related deaths in the world. The standard care for CIN is cervical cornification, which, however, increases risk of premature birth and newborn mortality due to a compromised cervix function (11)(12)(13)(14) and nearly 10% of recurrence risk by persisting HPV infection (15,16), and noninvasive therapeutics has been demanded for CIN treatment. Thus, in this study, we examined anti-HPV compound for a therapeutic effect on HPV-induced CIN and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%